Delayed sudden hearing recovery after treatment of a large vertebral artery aneurysm causing hearing loss and imbalance: a case report. (4th July 2022) - Nussbaum, Eric S.; Goddard, James K.; Lowary, Jodi; Robinson, Jenna M.; Hilton, Chris; Nussbaum, Leslie A.
Abstract: Purpose: Cerebral aneurysms that compress cranial nerve VIII can cause hearing loss and imbalance. Hearing function that does not recover after aneurysm occlusion can signal neurological damage with the potential for permanent deafness. Case Description: A 72-year-old woman presented with gradually worsening left-sided hearing loss and imbalance over a period of 10 years. She was found to have a lesion of the cerebellopontine angle, which proved to be a large fusiform vertebral artery aneurysm with mass effect on cranial nerve VIII. The patient underwent surgical clip occlusion of the vertebral artery distal to the posterior inferior cerebellar artery and proximal to the aneurysm, which no longer filled on catheter angiography. Postoperatively, the patient experienced delayed complete loss of ipsilateral hearing on the third post-operative day. Otherwise, she made a good recovery with improvement in her balance issues. At that time, we suspected that delayed occlusion of a perforating vessel had probably caused irreversible hearing loss. Ten months later, the patient awoke with significant subjective recovery of her hearing. Audiometry confirmed substantial improvement in her hearing likely due to the aneurysm shrinking away from and decompressing the cranial nerve. Conclusion: This case highlights the continued usefulness of vascular occlusion in the management of selected cases of intracranial aneurysms and also that neurological function may recover suddenly, even in very delayed fashion, following treatment.